Player position affects relationship between internal and external training loads during Division I collegiate female soccer season - Ishida, A.; Travis, S. K.; Draper, G.; White, J. B.; Stone, M. H. (The Journal of Strength and Conditioning Research, 2022)
The purpose of this study was to investigate how competition phase and player position affect the relationship between internal and external training loads (ITL and ETL, respectively) in collegiate female soccer. Seventeen players participated (21.8 ± 1.7 years; 165.1 ± 6.2 cm; and 63.7 ± 7.9 kg). Nineteen match-plays (10 nonconference and 9 conference) were completed during the 2019 competitive season, including 270 observations of 17 players (defenders = 5, midfielders = 9, and forwards = 3). Internal training load was assessed using session rating of perceived exertion (sRPE). External training load included total distance and high-speed running (HSR) distance. A linear mixed model was compiled with fixed effects of total distance, HSR, competition phase, and player position (defenders, midfielders, and forwards) and random effects of player. There were statistically significant main effects for total distance (p < 0.001), HSR (p = 0.047) and player position (p = 0.045) on the prediction model of sRPE. However, the main effect of competition phase did not statistically contribute to the prediction model of sRPE (p = 0.38). In the final model, total distance (p < 0.001) and player position for forwards (p = 0.008) were significant predictors of sRPE. However, there was no statistically significant fixed effect of HSR on sRPE (p = 0.15). The final model explained 60.6% of the variance in sRPE (R2 = 0.60), whereas the random effect also explained 6.1% of the variance (R2 = 0.06). Our findings indicated that total distance and player position were strong predictors of sRPE. The relationship between ITL and ETL should be monitored by player position in female soccer players.